PENGEMBANGAN MEDIA VIDEO PEMBELAJARAN UNTUK MATERI TEKSTIL PADA MATA PELAJARAN SENI BUDAYA DI SEKOLAH MENENGAH PERTAMA NEGERI 16 PADANG - Suci Rahayu WD, Drs. Wisdiarman, M.Pd., Dra. Zubaidah, M.Pd., (Universitas Negeri Padang, 2018)
This research aims to : 1) Develop learning video media for textile material at SMP N 16 Padang. 2) Knowing the feasibility (Validity), Praktikalitas and Effectiveness of learning video for textile media at SMP N 16 Padang. This type of Research Development (R&D). The subject of this research is the student of class VIII.1 A total of 32 student and the object of research is a video learning media for textile material in SMP N 16 Padang. The result of this development research are : 1)learning media video product for textile material which is very feasible with 100% percentage, practical with 78 % percentage and very effective with percentage 90,62%. So declaring video learning media for textile material class VIII feasible, practical, and effective.Keywords: Development, Media Video, Textile Material, SMP N 16 Padang.